Penanaman Nilai-Nilai Multikulturalisme Melalui Pengajaran Listening Menggunakan Lagu Islami Berbahasa Inggris - Santiandriyani Santiandriyani (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Indonesia is one of the countries that uphold the values ​​of multiculturalism. Indonesia is also a country that reflects the concept of multiculturalism with a variety of cultural wealth, customs, tribes, and also different religions. In fact, many conflicts that occur because of the differences. This paper is aimed at analyzing more deeply about the cultivation of multicultural values ​​through the teaching of Listening by using Islamic English songs in the album Salam by a young Muslim singer named Harris J. The writer uses the Dell Hyme's theory in analyzing a song in the album Salam. The results of this study shows that the content of the texts is related to 4 concepts of multiculturalism values, namely (1) tolerance, (2) democracy, (3) equality, and (4) justice. Based on the results of the study, the teaching of Listening through Islamic songs in English gives a significant impact on the cultivation of the multiculturalism values ​​for students.